The role of social networks in crisis communication - Mirenić, Ana; Stanilović, Lucija (Crisis Management Days, 2025)
This paper analyzes the role of social media in crisis communication, with a particular focus on the context of the Republic of Croatia. The aim of the research is to elucidate the potentials and challenges that social media present during crises, and to provide recommendations for effective and responsible management of communication under these conditions. In times of crisis, where information is often sensitive and urgent, social media become essential tools for the dissemination of messages as well as for interaction with the public. The study is grounded in a comprehensive theoretical framework that encompasses key concepts of crisis communication, media literacy, the phenomenon of misinformation, and the role of social media in shaping public opinion. By analyzing practical examples, the paper will explore how institutions have utilized these platforms for informing citizens, assessing crisis events, and managing situations requiring immediate communication. Particular attention will be paid to the communication strategies employed by the Croatian Institute of Public Health (HZJZ) and the Government of the Republic of Croatia during key crisis events, including the COVID-19 pandemic and the earthquakes in the Sisak-Moslavina County. This analysis will enable an assessment of the effectiveness of the communication strategies utilized and their impact on public trust. Based on the research findings, the paper will offer guidelines for optimizing crisis communication, with an emphasis on the responsible and effective use of social media to ensure timely and accurate information for citizens during future crisis situations.